PENGARUH ORIENTASI PASAR DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN PADA SENTRA INDUSTRI KECIL PEMBUATAN BAKPIA DI KABUPATEN BANTUL - Sarjita Sarjita (Jurnal Bisnis, Manajemen, dan Akuntansi, 2017)
This research is a test of the influence of market orientation and product innovation on marketing performance at small bakpia manufacturing center in Bantul regency. The number of business actors bakpia manufacture that continues to demand competitiveness in marketing their products. In this study, the population as well as samples are bakpia entrepreneurs in Bantul regency which amounted to 48 people with sampling technique conducted by census or total sampling. The variables in this study consist of: independent variable that is market orientation (X1) and product innovation (X2) and dependent variable that is marketing performance (Y). Data collection techniques used are questionnaires and documentation. Data analysis technique used in this research is multiple regression analysis. Keywords: Market Orientation, Product Innovation, Marketing Performance